Fotoluminescência do CaMoO4, MgTiO3 e b-ZnMoO4: um estudo teórico - Moraes, Eduardo de (2015)
In this work, calcium molybdate (CaMoO4) crystals, MgTiO3 (MTO) thin films and beta zinc molybdate (b-ZnMoO4) microcrystals were synthesized by the different methods and structurally characterized X-ray diffraction (XRD), Rietveld refinement, Fourier transform Raman (FT-Raman) and Fourier transform infrared (FT-IR) spectroscopies. A combined theoretical and experimental study on the electronic structure and photoluminescence (PL) properties these materials has been employed. Their optical properties were investigated by ultraviolet-visible (UV-vis) absorption spectroscopy and PL measurements. First-principles quantum mechanical calculations based on the density functional theory at the B3LYP calculation level have been carried out. The blue and green PL emissions observed in these crystals of the CaMoO4 were ascribed to the intermediary energy levels arising from the distortions on the [MoO4] clusters due to intrinsic defects in the lattice of anisotropic/isotropic crystals. Band structure and Density of states descried the levels energy and a direct gap (G-G). In principle, the theoretical data suggested a strong hybridization between the O 2p (above the VB) and Mo 4d orbitals (near the CB), respectively. Band structure results indicate an indirect band gap for ordered and disordered models of the MgTiO3 in different regions of the Brilouin zone and density of states (DOS) show creates new levels energy with the dislocated Ti atom. The charge maps were used in this structure to verify densities charge distributed asymmetrically, contributing to the formation densities of electrons and holes in the structure. With relation the b-ZnMoO4, the theoretically calculated results of IR and Raman frequencies are in agreement with experimental results. UV-vis absorption measurements shows an optical band gap value of 3.17 eV, while the calculated band structure has a value of 3.22 eV. The density of states indicate that the main orbitals involved in the electronic structure of b-ZnMoO4 crystals are oxygen 2p in the valence band and Mo 4d in the conduction band.